PENGARUH MOTIVASI KERJA DAN PENDIDIKAN PELATIHAN (DIKLAT) KEARSIPAN TERHADAP PRODUKTIVITAS KERJA PEGAWAI DI DINAS PERPUSTAKAAN DAN KEARSIPAN DAERAH PROVINSI JAWA BARAT - Nunung Nurhayati, - (2021)
Low productivity of employees is one of the interesting problems to be studied in the scope of human resource management. This can be seen from the realization of not achieving the targets planned by Dinas Perpustakaan dan Kearsipan Daerah Provinsi Jawa Barat. Factors that affect work productivity are work motivation and archival training and education. Based on this, the study of this research is to determine the effect of work motivation and archival training (education and training) on the work productivity of employees at Dinas Perpustakaan dan Kearsipan Daerah Provinsi Jawa Barat. The method used in this research is an explanatory survey and the data collection technique is using a questionnaire with respondents taken from a population of 38 people. The instrument used is a questionnaire using a rating scale. Data analysis used multiple regression analysis. Based on the results of the study, it was concluded that work motivation had a low relationship and a significant positive effect on work productivity, while archival training and education had a strong or high relationship and a significant positive effect on work productivity. Based on the results of the study, it was concluded that 1) work motivation had a positive and significant effect on work productivity, 2) archival training and education had a positive and significant effect on work productivity, 3) work motivation, education and training (training) archives had a positive and significant impact on work productivity. significant to work productivity. Keywords: Work Productivity, Archival Training and Education, Work Motivation